Partisipasi Pelaku Usaha Pariwisata dalam Pengelolaan Sampah di Pantai Pulang Sawal, Kabupaten Gunungkidul, Yogyakarta - Jussac Maulana Masjhoer (Jurnal Pariwisata Terapan, 2018)
Tourism business actors at Pulang Sawal Beach produce waste as many as tourists visit. The waste management issues at the beach area could affect the tourist’s comfort if the problems left unsolved. This study aims to determine the type of waste generated, as well as the participation of tourism business actors in waste management. The type of research used in this study is descriptive qualitative. The population in this study is a tourism business actor at Pulang Sawal Beach. The sampling method used in this study is simple random sampling. Data collection techniques are through observation, interviews, questionnaires, and documentation. The data obtained is then analyzed using qualitative analysis. The type of organic waste produced is in the form of food leftovers, raw materials leftovers, paper, cardboard, cartons, newspapers, etc. While the types of inorganic waste produced are plastic bags, food packaging, plastic and glass bottles, etc. The results showed that tourism business actors participated in the decision-making stage as much as 37%, participated in the implementation of 67.8%, participated in taking benefits as much as 100%, and participated in the evaluation phase as much as 95%. Low participation in decision making due to the lack of knowledge related to waste management, so they choose to listen and accept every decision that is made. They have not implemented good waste management. Tourism business actors agree that a clean business environment benefits both the convenience of work and visitors and assesses that waste management is in accordance with planning.